Vernal keratoconjunctivitis in human immunodeficiency virus – The possible role of T-helper 1–T-helper 2 shift - Shweta Agarwal; Bhaskar Srinivasan; Geetha Iyer; Sridharan Sudharshan; Kavita Kalaivani (Indian Journal of Ophthalmology, 2018)
Human immunodeficiency virus infection (HIV) is associated with a reduced T-helper (Th) 1 response, and vernal keratoconjunctivitis (VKC) occurs secondary to a heightened Th2 response. VKC has been reported to occur in patients with HIV. In all probability, a Th1–Th2 shift occurs in the immune response in progressive HIV patients with a decreasing CD4 count. This shift could be the probable cause for the initiation and gradual worsening of the VKC in our patient that corresponded to the dropping CD4 counts. VKC resolved only after a change in antiretroviral therapy for HIV that caused a demonstrable increase in the CD4 counts possibly by reversing the shift.